Design and Construction of A Remotely Controlled Multy-Tasking Chain-Wheel Combat Robot - Nur Rachman Supadmana Muda; M.Faisal Fadilah; Bilqis Faranadila; Dinar Safanabila (Eduvest - Journal of Universal Studies, 2024)
Troops in the context of reconnaissance or search tasks to find out the enemy in difficult, protected and disguised terrain is an element of vulnerability that needs to be taken into account. If you insist on finding out the enemy's condition, there is a possibility that contact will occur early and cause casualties which could thwart the main task. Therefore, a tool or robot is needed to help obtain data about protected enemies by diverting the enemy's attention and providing resistance. The aim of this research is to create a prototype chain-wheeled combat robot platform system that is capable of maneuvering, firing SS2 and rockets, detecting mine-prone areas, and detecting body thermals. The robot control system consists of a mobile controller and a base station. The mobile controller functions to control robot movements such as forward, backward, right turn, left turn, weapon azimuth movement, weapon elevation movement and shooting using 2.4 GHz radio control and target monitoring using FPV ((First person view) directly in the field on a frequency of 5.6 GHz, base station functions to control the robot's movement and monitor targets using a laptop via the internet. The robot system is equipped with GPS and a metal detector, so that the robot's position can be monitored and report the presence of mines to the base station. Thus, the robot created is expected to be able to help to combat duty in the context of war military operations.